Impact of stress on face skin - Červinskytė, Gintarė; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2021)
Stressors are detrimental to our skin, they may make the following chronic skin diseases more acute: erysipelas (a bacterial infection of the superficial layer of the skin (upper dermis), acne, dermatitis, psoriasis, eczema. Due to the experienced stress, face skin loses elasticity, aging processes are speeded up. It is very important to learn to manage stress, to choose adequate beauty products for face skin care. The aim of the investigation: to assess the efficiency of face skin procedures seeking to reduce skin problems that arise because of stress. Materials and methods of the investigation: a customer’s card created by the College of Social Sciences was used in the investigation: the use of cosmetics (beauty products) at home, the impact of stress on face skin and the lifestyle were elucidated, the condition of skin under investigation was assessed, a map of the condition of skin was compiled. Results and conclusions of the investigation. Prior to the first procedure skin-folds on the sides of the nose (nasolabial folds), between the eyes, wrinkles in the visible part of the eyelid and under the lip were determined. The skin has lost its radiance, there are single red spots on it (assessing visually), pores are clearly visible in the T-zone. After the fifth procedure radiance of the skin was restored and the skin became one tone lighter. The number of wrinkles under the eyes decreased, skin-folds on the sides of the nose and pores on the face became less noticeable. Conclusions. Stress stimulates the production of cortisol, too large amount whereof effects the face skin, which becomes thinner, loses its radiance, is more sensitive to external environmental factors. Adrenalin slows down circulation of the blood, capillaries of the derma become spasmodic, the skin can turn pale, red sports appear. Moisturising beauty products selected taking into consideration face skin problems caused by the stress and containing active ingredients stimulating the regeneration of the cells are highly efficient.